Shelterwood : a novel - Wingate, Lisa (New York : Ballantine Books, 2024)
"Oklahoma 1909. Eleven-year-old Olive Augusta Radley knows that her stepfather doesn't have good intentions toward the two Choctaw girls boarded in their home as wards. When the older girl disappears, Ollie flees to the woods, taking six-year-old Nessa with her. Together they begin a perilous journey to the rugged Winding Stair Mountains, the notorious territory of outlaws, treasure hunters, and desperate men. Along the way, Ollie and Nessa form an unlikely band with others like themselves, struggling to stay one step ahead of those who seek to exploit them... or worse. Oklahoma 1990. Law Enforcement Ranger Valerie Boren O'dell arrives at Horsethief Trail National Park seeking a quiet place to balance a career and single parenthood. But no sooner has Valerie reported for duty than she's faced with local controversy over the park's opening, a teenage hiker gone missing from one of the trails, and the long-hidden burial site of three children deep in a cave. Val's quest to uncover the truth wins an ally among the neighboring Choctaw Tribal Police, but soon collides with old secrets and the tragic and deadly history of the land itself. In this emotional and enveloping novel, Lisa Wingate traces the story of children abandoned by the law, and the battle to see justice done. Amid times of deep conflict over who owns the land and its riches, Ollie and Val traverse the wild and beautiful terrain, each leaving behind one life in search of another"--.
new book 2024 summer.
Includes bibliographical references.
Keywords: Women park rangers -- Fiction; Choctaw Indians -- Fiction -- Oklahoma; Missing children -- Fiction -- Oklahoma; Detective and mystery fiction; Novels; Historical fiction; Detective fiction; Mystery fiction